An archaeologist in Rome at the service of the Order - Cecalupo, Chiara, 1989- author. aut Link
1 online resource (vi, 220 pages).
Keywords: "An Archaeologist in Rome at the Service of the Order presents the so far completely unknown letters between the Grand Masters (Alof de Wignacourt, Luís Mendes de Vasconcellos, Antoine de Paule) and Antonio Bosio, well known worldwide for his extensive discoveries of the Roman Christian catacombs, but also Agent of the Order of Malta in Rome. The letters were sent between 1604 and 1629 and are currently held at the National Library of Malta. After a complete account on Bosio's biography and family history, the letters are transcribed, translated and commented, in order to open a window on the role of the Agent in Rome in the very early seventeenth century, a particular juncture in the Order's history, and on the relations between Malta and Rome. The study and publication of these materials make it possible to present Antonio Bosio's political and administrative work at the service of the Grand Master to the international public and academics interested in the history of the Order"-- Provided by publisher.